A study on the awareness of the weaning practices and the determinants affecting them in a rural hospital based pediatric outpatient clinic of Maval Taluka, Maharashtra - Ambike, Deepali; Bhavari, Vijay; Poker, Faisal; Ahmed, Kaenat (International Journal of Contemporary Pediatrics, 2016)
Background: Malnutrition and micronutrient deficiencies is a very common cause of late weaning and improper weaning practices. There are many factors affecting the weaning practices in developing countries like India which may act as hindrance to the proper weaning methods. The objective of this study was to know the awareness about weaning or complementary feeding practices in the mothers of children attending the pediatric OPD. And to study the various determinants affecting the weaning or Complementary feeding practices in this rural population. Methods: This study is a cross-sectional study conducted in pediatric immunization outpatient clinic of M.I.M.E.R medical college, Talegaon (D) during the period from May to September 2016.About 300 parents were interviewed with a semi open questionnaire. Results: Out of total 304 respondents, total unawareness regarding weaning was the reason for not starting complimentary feeding at 6-months in 64 respondents (21.1%). Majority of the respondents (210, 69.1%) revealed that they prefer home based complimentary feeding. A total of 125 respondents (41.1%) admitted that they stopped the feeding in the event of illness. Conclusions: Incorrect weaning practices, withholding breastfeeding and improper feeding during illnesses are the major deterrents which can hamper proper weaning techniques and are major contributory factors in increasing Malnutrition.